2011
DOI: 10.3109/00952990.2011.596874
|View full text |Cite
|
Sign up to set email alerts
|

Is Monogamy or Committed Relationship Status a Marker for Low Sexual Risk among Men in Substance Abuse Treatment? Clinical and Methodological Considerations

Abstract: Background HIV prevention interventions often promote monogamy to reduce sexual risk. However, there is little consensus about how to define monogamy. Objective Determine the extent to which recent monogamy and/or being in a committed relationship serve as markers for low sexual risk among men in substance abuse treatment. Methods Participants were 360 men enrolled in the NIDA Clinical Trials Network “Real Men Are Safe” protocol who completed all assessments (baseline, 3 months, 6 months). Self- reported b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Although some researchers contend that sexual risk (e.g., condomless sex) cannot exist within monogamous relationships (Calsyn, Campbell, Tross, & Hatch-Maillette, 2011), for the purpose of this study, sexual risk was defined as something that can occur within or outside of a monogamous relationship. As mentioned before, researchers have found that much of the sexual risk behavior that does occur among gay and bisexual men occurs within relationships (Sullivan et al, 2009).…”
Section: Attachment Theory and Sexual Risk Behaviormentioning
confidence: 99%
“…Although some researchers contend that sexual risk (e.g., condomless sex) cannot exist within monogamous relationships (Calsyn, Campbell, Tross, & Hatch-Maillette, 2011), for the purpose of this study, sexual risk was defined as something that can occur within or outside of a monogamous relationship. As mentioned before, researchers have found that much of the sexual risk behavior that does occur among gay and bisexual men occurs within relationships (Sullivan et al, 2009).…”
Section: Attachment Theory and Sexual Risk Behaviormentioning
confidence: 99%
“…That is, as it is currently practiced in contemporary Western cultures, "monogamy" does not necessarily mean that a partner is and always will be one's only sex partner. Moreover, monogamy is defined inconsistently in academic literature, and researchers do not consistently make distinctions between what people are actually practicing (e.g., serial monogamy, ostensible monogamy with infidelity) versus what is implied by the term monogamy, that is, a lifelong, or at least long-term, relationship with only one sexual partner (Calsyn et al, 2011).…”
Section: "I'm Monogamous With Whomever I'm With"mentioning
confidence: 99%
“…Second, opioid injection and other risk behaviors were assessed via interviews with trained research staff but are based on participant selfreport. Third, the RAB treats oral, vaginal and anal sex as equally risky sexual acts and does not distinguish condom use with a primary partner versus a casual partner, which may confer different HIV risks [57, 58]. Fourth, we did not enroll non-English speaking patients in the study, although several of the participants did speak English as a second language at a level sufficient to provide informed consent and complete study assessments.…”
Section: Discussionmentioning
confidence: 99%